Effects of Lecithin Addition on the Properties of Extruded Maize Starch. Issue 1 (7th October 2015) - Yang, Qingyu; Yang, Yong; Luo, Zhigang; Xiao, Zhigang; Ren, Haibin; Li, Demin; Yu, Jinping
Abstract: Normal maize starch combined with lecithin (LEC) was treated at a moisture content of 30% and screw speed of 160 rpm by extrusion processing. Extrusion treatment decreased the X‐ray intensities of maize starch, and the diffraction peak type of extrudates was changed from A to A + V. Extrusion processing increased the gelatinization temperature and decreased the gelatinization enthalpy. A drop in pasting temperature and viscosity of extrudates was found with increasing barrel temperature. Compared with native maize starch, scanning electron micrograph results showed that the surface was rough, distorted and the diameter of extrudate granule became bigger. The Fourier transform infrared analysis indicated that the characteristic peak at 1, 734/cm −1 was observed for maize starch LEC extrudates. The forgoing data suggested that the esterification of maize starch with LEC occurred during extrusion processing. This work provided a method for the production of esterified starch with LEC that can be used in the food industry. Practical Applications: This research had an objective to study the surface morphology, structure, viscosity and thermal properties. This study provided some basic information required for the production of low‐viscosity starch extrudates using maize starch blended with enhanced technological properties that are comparable with maize starch using lecithin. The starch extrudates have been successfully applied in ice cream and bakery processing. Understanding the formula and extrusion conditions to alter its functionality in puffed ingredients will benefit the food industry and will allow for the expanded use of this ingredient in extrudate maize starch. Understanding of the changes during extrusion processing between maize starch and lecithin is required for necessary processing actions and decisions.